1991
DOI: 10.1126/science.251.4998.1218
|View full text |Cite
|
Sign up to set email alerts
|

Auger Electron Angular Distributions from Surfaces: Direct Comparison with Isoenergetic Photoelectrons

Abstract: Angular distribution patterns of Auger electrons and of photoelectrons from a Cu (001) surface were measured at the same electron kinetic energy. These measurements reveal that the low kinetic energy angular distributions for Cu Auger electrons and Cu 3p(3/2) photoelectrons differ substantially. This direct comparison between the photoelectron and Auger electron angular distributions demonstrates that, in some circumstances, the Auger process produces a complicated source wave whose nature must be explored bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Interatomic directions in the crystal can be determined from these forward scattering spots, since at these kinetic energies the greatest intensity is found in the forward scattering direction when the emitter, scatterer, and detector are aligned. 1,2, 19 The simplest way to do this is to compare the experimental results with the plots shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interatomic directions in the crystal can be determined from these forward scattering spots, since at these kinetic energies the greatest intensity is found in the forward scattering direction when the emitter, scatterer, and detector are aligned. 1,2, 19 The simplest way to do this is to compare the experimental results with the plots shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Early experiments assumed that Auger electrons could be treated as s waves with an isotropic angular distribution, 16,17 but more recent work has shown that it is important to take the angular momentum of the outgoing Auger electron wave into account. 18,19 To take the Auger electron angular momentum into account, we have performed calculations for electrons with different values of the angular momentum quantum number l. In Fig. 8 Fig.…”
Section: Fig 3 Schematic Representations Of the Scattering Directiomentioning
confidence: 99%
See 2 more Smart Citations
“…different final state angular momenta, at constant energy, and should therefore be very important to further our understanding of this interplay. One such study has recently been published by Terminello and Barton [26], comparing the patterns of Cu Μ2,3Μ4,5Μ4,5 and Cu 3p emission from Cu(001), both at 60 eV. Their results indicate that the source wave effects are very important at this energy.…”
Section: Two-dimensional Intensity Measurementsmentioning
confidence: 99%